2015
DOI: 10.1021/acsnano.5b01048
|View full text |Cite
|
Sign up to set email alerts
|

Phage-Display-Guided Nanocarrier Targeting to Atheroprone Vasculature

Abstract: In regions of the circulation where vessels are straight and unbranched, blood flow is laminar and unidirectional. In contrast, at sites of curvature, branch points and regions distal to stenoses blood flow becomes disturbed. Atherosclerosis preferentially develops in these regions of disturbed blood flow. Current therapies for atherosclerosis are systemic, and may not sufficiently target these atheroprone regions. In this study, we sought to leverage the alterations on the luminal surface of endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…19 Moreover, administration of BH 4 also prevents the development of endothelium dysfunction, vascular inflammation and atherosclerosis induced by disturbed flow. 20, 21 Acute and short-term administration of BH 4 improves endothelial function in humans with rheumatoid arthritis. 22 There is also convincing evidence that eNOS uncoupling occurs in humans with obstructive sleep apnea, leading to increased vascular superoxide production and endothelial dysfunction.…”
Section: Nitric Oxide Synthase Uncoupling and Tetrahydrobiopterinmentioning
confidence: 99%
“…19 Moreover, administration of BH 4 also prevents the development of endothelium dysfunction, vascular inflammation and atherosclerosis induced by disturbed flow. 20, 21 Acute and short-term administration of BH 4 improves endothelial function in humans with rheumatoid arthritis. 22 There is also convincing evidence that eNOS uncoupling occurs in humans with obstructive sleep apnea, leading to increased vascular superoxide production and endothelial dysfunction.…”
Section: Nitric Oxide Synthase Uncoupling and Tetrahydrobiopterinmentioning
confidence: 99%
“…[ 5 ] Hence, the anti‐inflammatory effects ( Figure A) of BMSC‐NVs, ASC‐NVs, and PMSC‐NVs were examined. In particular, since our previous study reported that monocyte/macrophage could uptake PREY‐liposome, [ 12 ] mouse bone marrow‐derived macrophages (BMDMs) obtained after primary culture or the mouse macrophage cell line (Raw 246.7) were treated with the MSC‐NVs to inhibit their inflammatory responses. First, the effective cellular uptake of the MSC‐NVs (ASC‐NVs, BMSC‐NVs, and PMSC‐NVs) by the activated BMDMs was confirmed by visualization with DiI and DiO, respectively (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…An in vivo imaging system (IVIS) was used to visualize their biodistribution at 24 h post‐injection ( Figure A,B; Figure S10, Supporting Information). Since we previously demonstrated that a scrambled peptide of the PREY sequence had no significant targeting effect, [ 12 ] no peptide control group was included in this study. The LCA‐targeting efficiency of PMSC‐NVs was better than that of MSC‐NVs or PMSCs, indicating the synergistic roles of PREY and NV to hinder the pulmonary capillary entrapment of cells and thereby to effectively target disturbed flow sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen’s group[35] used the synthetic peptide ACSSSPSKHCG to improve the transdermal delivery of proteins such as human growth hormone and insulin. Hofmeister et al[36]found that the peptide GSPREYTSYMPH (PREY) could guide the nanocarriers to bind to atherosclerotic vasculature.…”
Section: Phage Displaymentioning
confidence: 99%